2014
DOI: 10.3389/fcimb.2014.00150
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between type three secretion system and metabolism in pathogenic bacteria

Abstract: Before the advent of molecular biology methods, studies of pathogens were dominated by analyses of their metabolism. Development of molecular biology techniques then enabled the identification and functional characterisation of the fascinating toolbox of virulence factors. Increasing, genomic and proteomic approaches form the basis for a more systemic view on pathogens' functions in the context of infection. Re-emerging interest in the metabolism of pathogens and hosts further expands our view of infections. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 89 publications
(121 reference statements)
1
9
0
Order By: Relevance
“…Other factors might participate in the reduction of virulence of FPC1214. Interrelationship between pyruvate pathway and expression of T3SS has been reported in Aeromonas hydrophila, E. coli or Salmonella enterica (Wilharm and Heider, 2014). In the present study, phosphonopyruvate decarboxylase (Ppd) and phosphoenolpyruvate phosphomutase (Ppm) were found only in FPC1091.…”
Section: Discussionsupporting
confidence: 46%
“…Other factors might participate in the reduction of virulence of FPC1214. Interrelationship between pyruvate pathway and expression of T3SS has been reported in Aeromonas hydrophila, E. coli or Salmonella enterica (Wilharm and Heider, 2014). In the present study, phosphonopyruvate decarboxylase (Ppd) and phosphoenolpyruvate phosphomutase (Ppm) were found only in FPC1091.…”
Section: Discussionsupporting
confidence: 46%
“…It is currently unclear whether the suppression of growth during secretion is based on the leakage of ions and amino acids, which might be either co-transported with the secreted proteins or passively diffuse through the T3SS during secretion (Fowler and Brubaker, 1994; Fowler et al, 2009), the metabolic burden caused by biosynthesis, assembly and operation of the T3SS (Brubaker, 2005; Sturm et al, 2011; Wilharm and Heider, 2014; Wang et al, 2016), yet unknown specific regulatory mechanisms, or a combination thereof. Wang et al showed that in the related Y. pseudotuberculosis , activation of the T3SS by Ca 2+ chelation or host cell contact leads to an increased copy number of the virulence plasmid (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…pseudotuberculosis and P. aeruginosa [76,125,126]. Finally, the glyoxylate shunt has been implicated in pathogenesis of organisms in human disease [127].…”
Section: Metabolism and Pathogenicitymentioning
confidence: 99%